'Better than a pill': digital storytelling as a narrative process for refugee women. Issue 1 (2nd January 2019) - Lenette, Caroline; Brough, Mark; Schweitzer, Robert D.; Correa-Velez, Ignacio; Murray, Kate; Vromans, Lyn
ABSTRACT: Digital storytelling is a valuable and ethical research tool to engage in collaborative research with refugee women. This paper recounts how digital storytelling was used in a mixed-methods study on settlement, to document the journeys of women who entered Australia through the Woman at Risk program in 2014–2015. Instead of merely asking a series of questions, the digital storytelling process extended our qualitative inquiry as an approach that valued the women's own memories, interests, and hopes. The methodology represents a meaningful way of engaging in collaborative research, where participating women were not just storytellers but valued as active co-constructors of new knowledge. We outline each of three digital narratives as a 'whole' to consider what we can learn from a storytelling process where women with complex circumstances are privileged as protagonists-and-producers of their own stories. We argue that it is worth critically reflecting on the concepts the women propose for themselves as meaningful ways to articulate their lives, when we relinquish the researcher role as question asker to enter a space alongside participants and listen intently. Our paper highlights the broader potential of digital storytelling particularly in mental health research in collaboration with refugee participants.